Letter : Voluntary industrial aid - Pyke, Geoffrey
036-0026-001 VOLUNTARY INDUSTRIAL AID FOR SPAIN TELEPHONE: HOLBORN 6119 32 GREAT ORMOND STREET LONDON, W.C.1 8th May 1937 ADVISORY COMMITTEE: HARRY ADAMS, Chairman (Amalgamated Union of Building Trade Workers) ALFRED BARNES, M.P. (Chairman of the Co-operative Party) A.C BASSEBE (Hydraulic Coupling Co., Ltd.) H.G. BROTHERTON (Sheet Metal Workers Union) A.W. COSTER Electrical Trades Union) J. DUNNAGE. A.M. Inst., T. J. DAGGER (Amalgamated Society of Woodcutting Machinists) R.H. EDWARDS (National Union of Vehicle Builders) LORD FARINGDON BERT JOY (Amalgamated Society of Woodworkers) GEOFFREY PYKE, Hon. Secretary J. REEVES (Royal Arsenal Co-operative Society) JOE SCOTT, Treasurer (Amalgamated Engineering Union) J.R. SHANLEY (Amalgamated Union of Upholsterers) JACK TANNER (Amalgamated Engineering Union) Councillor D.C. WEBSTER, L.C.C. (National Union of Vehicle Builders) A.M. WALL (London Trades Council) GP/EC Sir Walter Citrine, K.B.E. The Trades Union Congress General Council Transport House Smith Square London S.W.1. Dear Sir Walter, VOLUNTARY INDUSTRIAL AID. I write merely to acknowledge your letter of the 7th May, with many thanks. You will be glad to hear that we have been able to arrange that, should mattresses be needed for the refugee women and children coming to this country from Bilbao, two of the biggest and best firms will allow their premises to be used by voluntary labour, after hours, on a "no profit no loss" basis. I understand too that the workers will be willing to give their services overtime for this purpose. But of course all this could be done on a bigger and much more variegated scale, and everything arranged much more quickly, with the help of the T.U.C. Yours faithfully Geoffrey Pyke HON. SEC., VOLUNTARY INDUSTRIAL AID FOR SPAIN. 292/946/36/26